2009
DOI: 10.1111/j.1747-0803.2009.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Octopus Papillary Muscle Associated with a Left Lateral Accessory Pathway

Abstract: Left ventricular papillary muscle abnormalities are rare malformations. They have been related to significant mitral valve dysfunction and left ventricular midcavitary obstruction. We report our experience with a young adult who presented with palpitations. An echocardiogram on the patient showed an "octopus-like" left ventricular papillary muscle. Subsequent electrophysiologic testing showed evidence of supraventricular tachycardia via a left lateral accessory pathway associated with the abnormal insertion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…These attachments and bands may form a network in the LV cavity, previously described as the “Octopus papillary muscle” or “starfish like atypical parachute mitral valve” 4,5 . Octopus papillary muscle, first described by Shah A et al., is an embryological developmental abnormality causing a single central papillary muscle with fan shaped symmetrical radial extensions to all the walls of the LV, including the septum and resembling an octopus on parasternal short axis view 4,6 . While starfish like atypical parachute mitral valve shows two papillary muscles which get fused in mid LV cavity and have trabecular apical attachments resembling a starfish on apical two chamber veiw 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These attachments and bands may form a network in the LV cavity, previously described as the “Octopus papillary muscle” or “starfish like atypical parachute mitral valve” 4,5 . Octopus papillary muscle, first described by Shah A et al., is an embryological developmental abnormality causing a single central papillary muscle with fan shaped symmetrical radial extensions to all the walls of the LV, including the septum and resembling an octopus on parasternal short axis view 4,6 . While starfish like atypical parachute mitral valve shows two papillary muscles which get fused in mid LV cavity and have trabecular apical attachments resembling a starfish on apical two chamber veiw 5 .…”
Section: Discussionmentioning
confidence: 99%
“…ABMB, apical basal muscle bundle.shows two papillary muscles which get fused in mid LV cavity and have trabecular apical attachments resembling a starfish on apical two chamber veiw 5. Identifying uncommon variations in papillary muscles is crucial, as they can occasionally lead to obstruction in the mid cavity of the left ventricle or be linked to an accessory pathway 4,6. However, in this particular case, the presence of two clearly developed papillary muscles (Figure8; Video 7) and their attachment solely to the apical septum of the heart, rather than the whole LV, sets it apart from previously documented rare variations.Lack of LGE and presence of all three layers of cardiac tissue with preserved contractility throughout the LV ruled out possibility of pseudoaneurysm or post infarct aneurysm.…”
mentioning
confidence: 99%
“…The accessory papillary muscles aligned in radial symmetry to all the LV walls, which is called an octopus papillary muscle, causing mid‐ventricular obstruction. Patel et al reported another case of octopus papillary muscle with abnormal closure of the mitral valve with mild‐to‐moderate regurgitation. In our case, an anomalous hypertrophic papillary muscle and an additional discrete ridge connected to the septum and the papillary muscle, causing LV obstruction, might be etiologically and physiologically similar to the octopus papillary muscle.…”
Section: Discussionmentioning
confidence: 99%